2000
DOI: 10.1055/s-2000-8849
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Lactate Concentration in Preserved Blood Microsamples

Abstract: This study aimed to determine the stability of lactate concentration in blood samples preserved and stored using methods practical for field testing and experimental applications. Whole blood microsamples were obtained from venous samples drawn from 10 healthy subjects following bouts of moderate (approximately 5 mmol x l(-1), n = 12), or intense (approximately 10 mmol x l(-1), n = 12), treadmill exercise. Samples were analysed fresh (2 x 25 microl), or placed in preservative-containing tubes (12 x 75 microl) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…The current study used highly trained athletes, while our previous studies used healthy, but not trained, individuals. Indeed, previous studies have demonstrated an increased use of lactate as a fuel after exercise training (Bergman et al, 1999;Miller et al, 2002b), and that exogenous lactate infusion results in a decrease in glucose oxidation (Miller et al, 2002a). A second consideration is that exercise in the current study was performed at much higher flux rates than in our previous studies.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The current study used highly trained athletes, while our previous studies used healthy, but not trained, individuals. Indeed, previous studies have demonstrated an increased use of lactate as a fuel after exercise training (Bergman et al, 1999;Miller et al, 2002b), and that exogenous lactate infusion results in a decrease in glucose oxidation (Miller et al, 2002a). A second consideration is that exercise in the current study was performed at much higher flux rates than in our previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…The sodium lactate infusion was mixed according to previously described procedures (Miller et al, 2002a(Miller et al, , 2002b. Briefly, a USP-certified 88% lactic acid solution (Sigma Chemical, Auckland, NZ) was mixed in USP-certified 2 n NaOH to a pH of 4.8.…”
Section: Infusion Protocolmentioning
confidence: 99%
See 3 more Smart Citations